Experimental study of heat transfer parameters of s errated plate fin heat exchanger for different materials - Mr. S. V.Jagtap; Prof. A.M. Patil; Mr. D. D. Shinde (International Journal of Innovations in Engineering Research and Technology, 2021)
The heat transfer and flow friction Characteristics of plate fin surfaces are presented in terms of the Colburnfactor j and the Fanning friction factor f verses Reynolds numberRe, the relationships being different fordifferent surfaces. The laminar flow model predicts j and f valuesat low Reynolds number; the data isthroughout the range of interest. Velocity and temperature fields havebeen Computed and j and f factorsdetermined over appropriate range of Reynolds number and geometric dimensions. For this work I havedesigned heat exchanger according to procedure of design of serrated plate fin heat exchanger [12], Correlationused for finding various heat transfer parameters having Reynolds number less than 200 [6]. Experimental setupwas manufactured using calculated parameters of design. The effects of the materials Brass and Copper SPFHEon the heat transfer enhancement and friction factor behaviors in laminar flow regimes (Re < 200) are described.The fin dimension of serrated type plate fin heat exchanger SPFHE(H=3mm, t=0.2mm, s=2.5, lf=5mm for hotfluid and H=9.5mm, t=0.2mm, s=, lf=5mm for Cold fluid) same for both materials. On this setup readings weretaken by varying flow rate of hot oil, at Constant air for different temperatures of selected materials. Aftergetting readings Calculations were done for heat transfer parameters like Reynolds number, Colburn factor andFanning friction factor.